The Potential of Menstrual Blood-Derived Mesenchymal Stem Cells for Cartilage Repair and Regeneration: Novel Aspects - I. Uzieliene; G. Urbonaite; Z. Tachtamisevaite; A. Mobasheri; E. Bernotiene (Stem Cells International)
Menstrual blood is a unique body fluid that contains mesenchymal stem cells (MSCs). These cells have attracted a great deal of attention due to their exceptional advantages including easy access and frequently accessible sample source and no need for complex ethical and surgical interventions, as compared to other tissues. Menstrual blood-derived MSCs possess all the major stem cell properties and even have a greater proliferation and differentiation potential as compared to bone marrow-derived MSCs, making them a perspective tool in a further clinical practice. Although the potential of menstrual blood stem cells to differentiate into a large variety of tissue cells has been studied in many studies, their chondrogenic properties have not been extensively explored and investigated. Articular cartilage is susceptible to traumas and degenerative diseases, such as osteoarthritis, and has poor self-regeneration capacity and therefore requires more effective therapeutic technique. MSCs seem promising candidates for cartilage regeneration; however, no clinically effective stem cell-based repair method has yet emerged. This chapter focuses on studies in the field of menstrual blood-derived MSCs and their chondrogenic differentiation potential and suitability for application in cartilage regeneration. Although a very limited number of studies have been made in this field thus far, these cells might emerge as an efficient and easily accessible source of multipotent cells for cartilage engineering and cell-based chondroprotective therapy.